2020
DOI: 10.1038/s41598-020-66741-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of genetic variants in clinical outcome of a cohort of patients with oropharyngeal squamous cell carcinoma

Abstract: Tobacco- or human papillomavirus- driven oropharyngeal squamous cell carcinomas (OpSCC) represent distinct clinical, biological and epidemiological entities. The aim of this study was to identify genetic variants based on somatic alterations in OpSCC samples from an admixed population, and to test for association with clinical features. The entire coding region of 15 OpSCC driver genes was sequenced by next-generation sequencing in 51 OpSCC FFPE samples. Thirty-five percent of the patients (18/51) were HPV-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…A recent study of de Carvalho et al has shown that HPV-negative OPSCC tumors usually have a high mutation burden respect to HPV-positive ones [ 41 ]. In particular, TP53 mutations are frequently found in OPSCC driven by alcohol and tobacco, whereas their presence has been reported in only a small subset of HPV-related OPSCC so far [ 42 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of de Carvalho et al has shown that HPV-negative OPSCC tumors usually have a high mutation burden respect to HPV-positive ones [ 41 ]. In particular, TP53 mutations are frequently found in OPSCC driven by alcohol and tobacco, whereas their presence has been reported in only a small subset of HPV-related OPSCC so far [ 42 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies conducted to elicit whether particular somatic mutations are identified in this cohort of patients, in an attempt to correlate which patients are associated with a worse overall outcome. NOTCH1 and PTEN mutations were linked with a reduced recurrence free survival in patients with HPV positive OPSCC ( de Carvalho et al, 2020 ), with PIK3CA mutations linked with reduced disease free survival in those on de-intensified CRT ( Beaty et al, 2019 ). Conversely, FGFR3 mutations in HPV positive OPSCC are linked with improved disease free survival ( BERSANI et al, 2018 ).…”
Section: Human Papilloma Virus Positive Oropharyngeal Squamous Cell Carcinoma Linked With Disease Progression/recurrencementioning
confidence: 99%
“…However, infection with the Human Papilloma Virus (HPV) high-risk types are increasingly detected and currently considered one oncogenic driver in a subset of cases [ 2 ]. HNSCCs also harbor a high genetic heterogeneity, with mutations in tumor suppressor genes such as TP53 and p16INK4a and activation of oncogenes, such as the epidermal growth factor receptor ( EGFR ) and PIK3CA [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%